Mycological Study of Contaminated of the Burn Wounds in Baghdad City: Muna Hamudi Al Jubori, Jasim Mohamed Al-Hadithi, Rusol Muhammed Al Bahrani - Al Jubori, Muna Hamudi (The Iraqi Journal of Veterinary Medicine, 2011)
This study included 150 swabs were taken from patients was sufferingfrom different burns. The most common fungi isolated from burn wound wereAspergillus spp. (44.0%) at 37o and (38.17%) at 25o which include Aspergillusniger (9.31%) at 37o and (12.42%) at 25o , Aspergillus fumigatus (4.34%) at 37oand (10.55%) at 25o and Aspergillus flavus (0%) at 37o and (9.93%) at 25o ,followed by Candida spp. (7.45%) at 37o and (7.45%) at 25o, Which includesBlastomyces dermatitidis (0.62%) at 37o and (0.62%) at 25o, Helminthosporum(0%) at 37o and (0.62%) at 25o, Trichophyton terrestre (0%) at 37o and (0.62%)at 25o and Microsporum ajelloi (0%) at 37o and (0.62%) at 25o.The results ofminimal inhibitory concentration of anti fungal agents against Candida albicans, Candida glabrata , Candida krusei and Candida parapsilosis, Penicillium(1.66%) at 37o and (9.31%) at 25o, Alternaria (1.24%) at 37o and (3.72%) at 25o,Rhizopus (1.24%) at 37o and (2.48%) at 25o, Fusarium (1.24%) at 37o and(1.24%) at 25o, Mucor (0.62%) at 37o and (1.86%) at 25o, CladosporiumCarnoni (0%) at 37o and (1.86%) at 25o, Saccharomyces cerevisiae (0.92%) at37o and (1.24%) at 25o, Trichophyton rubrum (0%) at 37o and (1.24%) at 25o,Trichophyton verrucosum (0.62%) at 37o and (0.62%) at 25o, Candida albicansincreasing in order as 50  g /ml to Nystatin, 150 g /ml to Gention violet, 250 g /ml to Amphotericin–B, 300 g /ml to Clotrimazol, 950 g /ml to Benzoicacid and the later 1000  g /ml to copper Sulfate and Malachite green.